Air nanobubble-enhanced combustion study using mustard biodiesel in a common rail direct injection engine. Issue 15 (3rd August 2019) - Gobinath, S.; Senthilkumar, G.; Beemkumar, Nagappan
ABSTRACT: Though the biodiesel is environmental friendly than the conventional petroleum diesel in the aspects of better combustion quality due to higher cetane number (up to 65), reduced emission, and reduced air pollution, running the common rail direct injection (CRDI) engine with 100% biodiesel is not viable due to NO x and CO emissions. The present experimental investigation revealed that the above difficulty can be controlled by running CRDI engine with air nanobubble (ANBs)-enabled biodiesel. The results indicated that there was a reduction of 25% in brake-specific fuel consumption, 33% in NO x, and 16% in CO due to the addition of ANBs with mustard oil biodiesel.